Residual service stresses on tread of P65 rail - V. I. Sakalo; A. V. Sakalo (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The problems of rail durability and methods of forecasting it in conditions of increasing traffic density continue to be relevant. High stresses occur in the area of contact between the wheel and the rail, caused by the efforts of their interaction. They are considered in assessing contact strength of rails, and for their calculations effective and proven methods were developed. In addition to contact stresses rails contain residual process stresses that appear during cold straightening and thermal hardening, but these stresses undergo changes during rail operation. These stresses are not well studied. The distributions of technological residual stresses in the inner points of the rail are obtained by computational and experimental methods. Service residual stresses were studied by X-ray method mainly for rails made of foreign grades of steels with a long service life. The aim of the article is to determine the residual service stresses on the tread of P65 rail under the inf luence of long-term force action of the wheels of heavy-load cars.Materials and methods. In order to determine the residual service stresses on the tread of rail, a 750 mm long piece of rail was used. It has been in service for 20 years in heavy traff ic transit. The deformations were measured using the electric strain gauge measuring method. Strain gauges with a base of 5 mm and a resistance of 52.4 Ohms were used for measurement. Longitudinally, 9 strain gauges were glued in parallel to the rail axis, and 4 strain gauges were glued transversely. The stress relaxation method was used to determine the residual stresses.Results. The authors obtained distributions of longitudinal and transverse residual service stresses over the width of the tread of rail and performed their analysis.Discussion and conclusion. The obtained values of the longitudinal and transverse residual service stresses at the points of the tread of rail are in agreement with the results obtained by other authors using X-ray methods. When examining residual stresses in rails with sufficiently long service life using X-ray methods, it was found that the greatest stresses of approximately the same value arise in a subsurface layer with a thickness of about 10 mm. In this layer, there is the greatest probability of fatigue cracks. Considering the obtained residual stresses in the methods of modeling the processes of accumulation of rolling contact fatigue damage would allow to improve them and increase the accuracy of the obtained results.